Salivary microbiome of an urban Indian cohort and patterns linked to subclinical inflammation - Acharya, A; Chan, Y; Kheur, S; Kheur, M; Gopalakrishnan, D; Watt, RM; Mattheos, N (Oral diseases, 2017)
Objective To profile salivary microbiomes of an urban‐living, healthy Indian cohort and explore associations with proinflammatory status. Methods Fifty‐one clinically healthy Indian subjects’ salivary microbiomes were analyzed using 16S rRNA Illumina MiSeq sequencing. Community distribution was compared with salivary data from the Human Microbiome Project (HMP). Indian subjects were clustered using microbiome‐based “partitioning along medoids” (PAM), and relationships of interleukin‐1 beta levels with community composition were analyzed. Results Indian subjects presented higher phylogenetic diversity than HMP. Several taxa associated with traditional societies gut microbiomes (Bacteroidales, Paraprevotellaceae, and Spirochaetaceae) were raised. Bifidobacteriaceae and Lactobacillaceae were approximately fourfold greater. A PAM cluster enriched in several Proteobacteria, Actinobacteria, and Bacilli taxa and having almost twofold higher Prevotella to Bacteroides ratio showed significant overrepresentation of subjects within the highest quartile of salivary interleukin‐1 beta levels. Abiotrophia, Anaerobacillus, Micrococcus, Aggregatibacter, Halomonas, Propionivivrio, Paracoccus, Mannhemia, unclassified Bradyrhizobiaceae, and Caulobacteraceae were each significant indicators of presence in the highest interleukin‐1 beta quartile. 2 OTUs representing Lactobacillus fermentum and Cardiobacterium hominis significantly correlated with interleukin‐1 beta levels. Conclusion The salivary microbiome of this urban‐dwelling Indian cohort differed significantly from that of a well‐studied Western cohort. Specific community patterns were putatively associated with subclinical inflammation levels.